Mesothelial cells in tissue repair and fibrosis - Mutsaers, Steven E.; Birnie, Kimberly; Lansley, Sally; Herrick, Sarah E.; Lim, Chuan-Bian; Prêle, Cecilia M. (Frontiers in Pharmacology, 2015)
Mesothelial cells are fundamental to the maintenance of serosal integrity and homeostasis and play a critical role in normal serosal repair following injury. However, when normal repair mechanisms breakdown, mesothelial cells take on a profibrotic role, secreting inflammatory, and profibrotic mediators, differentiating and migrating into the injured tissues where they contribute to fibrogenesis. The development of new molecular and cell tracking techniques has made it possible to examine the origin of fibrotic cells within damaged tissues and to elucidate the roles they play in inflammation and fibrosis. In addition to secreting proinflammatory mediators and contributing to both coagulation and fibrinolysis, mesothelial cells undergo mesothelial-to-mesenchymal transition, a process analogous to epithelial-to-mesenchymal transition, and become fibrogenic cells. Fibrogenic mesothelial cells have now been identified in tissues where they have not previously been thought to occur, such as within the parenchyma of the fibrotic lung. These findings show a direct role for mesothelial cells in fibrogenesis and open therapeutic strategies to prevent or reverse the fibrotic process.